Pelatihan Microsoft Word Dalam Meningkatkan SoftSkill Pada Siswa/i SMK AL-Ma'Mun Education Center (AMEC) - Maulana Eka Prasetyo Maksum; Guruh Guniawan; Bayu Adi Prasetia; Muhamad Ihsan Daulay; Bayu Setiawan; Rafael Muhmad Gibran; Aida Fithrotun Nisa; Dian Tiara Devi; Raihana Mutiarawati; Syifa Khoirunnisa (Abdi Jurnal Publikasi, 2023)
Microsoft Office applications are very important to use in digital documenting, whether in the form of text, numbers and presentations. With the use that is increasingly in demand by various groups, both the office sector and the world of education. The development of Microsoft Office applications every year makes it difficult for students to follow its development. For this reason, training activities were made in the context of community service, which aims to increase knowledge and understanding of school students, especially vocational high schools (SMK) in using Microsoft Office, especially Microsoft Word which can be used or implemented in learning activities. With the training conducted they can use computers or laptops to do school work properly, such as writing papers or reports. Students gave a very positive response to the activities carried out and considered this activity very useful for the future.